Eksplorasi Ekplorasi Potensi Sumber Daya Alam dan Budaya Lokal serta Analisis Pengembangan Agro-Ekowisata Bale Tani Jombang: Ekplorasi Potensi Sumber Daya Alam dan Budaya Lokal serta Analisis Pengembangan Agro-Ekowisata Bale Tani Jombang - Farida, Laily Nur; Nurhidayah, Indah; Wahyudi, Muhammad Zainal Dwi; Sarjana, Budi; Sholihah, Fatikhatun Nikmatus (Exact Papers in Compilation (EPiC), 2025)
Agritourism is a form of tourism activity that utilizes the potential of agricultural businesses, including agricultural technology and agricultural commodities. In agritourism, the activities carried out include land preparation, maintenance, harvesting, processing of crops until the product is ready for market. Context in Bale Tani Agrotourism, it is important to identify the processing that is carried out. This includes understanding how local communities adapt from the traditional agricultural sector to agritourism management. The adaptation process of local communities in managing agritourism is very important to understand because it can provide insight into the sustainability of this business. Through this research, it is hoped that effective strategies can be found in agritourism management that are not only economically profitable but also strengthen social relations between community members and preserve the environment. This research is a descriptive qualitative research that aims to describe and analyze the management of agritourism in Bale Tani Jombang. Based on the results of interviews conducted with managers, Bale Tani agritourism in Jombang, East Java, is a tourist destination that combines the concepts of recreation and agricultural education. The tourist destinations that can be found in Bale Tani are very diverse, which include, Bale Derita, educational packages, Outbound packages, Spot games or can be said to be like a mini outbound place, Swimming pools and other facilities.